2017
DOI: 10.1186/s13643-017-0493-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective potential of N-acetyl cysteine against hyperglycaemia-induced oxidative damage: a protocol for a systematic review

Abstract: BackgroundHyperglycaemia-induced oxidative damage is a well-established factor implicated in the development of diabetic cardiomyopathy (DCM) in diabetic individuals. Some of the well-known characteristics of DCM include increased myocardial left ventricular wall thickness and remodelling that result in reduced cardiac efficiency. To prevent this, an increasing number of pharmacological compounds such as N-acetyl cysteine (NAC) are explored for their antioxidant properties. A few studies have shown that NAC ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Oxidative stress is well known to play a negative role in the development of chronic vascular complications, especially in patients with diabetes mellitus (DM) [32]. In diabetic cardiomyopathy (DCM), myocardial apoptosis is directly related to the generation of ROS in the heart, which is considered to be critical in the development and progression of DCM [97][98][99].…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…Oxidative stress is well known to play a negative role in the development of chronic vascular complications, especially in patients with diabetes mellitus (DM) [32]. In diabetic cardiomyopathy (DCM), myocardial apoptosis is directly related to the generation of ROS in the heart, which is considered to be critical in the development and progression of DCM [97][98][99].…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…The current cumulative line of evidence strongly suggests that NAC may have a role in being utilized as a cardioprotective agent by reducing hyperglycemia induced oxidative damage to cardiac myocytes and cardiac remodeling ( Chen et al., 1985 ; Dludla et al., 2017 ). This reduction in oxidative stress attenuates a progressive loss in cardiac efficiency and cardiac fibrosis that would have progressed to more severe clinical outcomes prior to intervention ( Seddon et al., 2007 ; Talasaz et al., 2013 ).…”
Section: Antioxidants In Ameliorating Obesity and Associated Comorbidmentioning
confidence: 99%
“…This reduction in oxidative stress attenuates a progressive loss in cardiac efficiency and cardiac fibrosis that would have progressed to more severe clinical outcomes prior to intervention ( Seddon et al., 2007 ; Talasaz et al., 2013 ). Data from multiple studies indicated that NAC elevated levels of SOD and glutathione in cardiac myocytes, while reducing levels of TGF-β, lipid hydroperoxides and various biomarkers for oxidative stress ( Haleagrahara et al., 2011 ; Talasaz et al., 2013 ; Dludla et al., 2017 ). Obesity and T2DM both exhibit a characteristic feature of hypercoagulable states through chronic inflammation associated with obesity and dysregulation of platelet aggregation ( Anderson and Weitz, 2010 ; Blokhin and Lentz, 2013 ; Widjaja et al., 2019 ).…”
Section: Antioxidants In Ameliorating Obesity and Associated Comorbidmentioning
confidence: 99%
“…NAC -is well-known synthetic mucolytic agent with AO properties due to its SH-group and ability to synthesize reduced glutathione. Lately, the possibility of NAC usage in correction of cardiovascular complications in case of diabetes mellitus has been actively discussed [9]. In experimental works, NAC increased activity of aldehyde dehydrogenase 2 -a key cardioprotective enzyme susceptible to oxidative inactivation in diabetic heart [8].…”
Section: Statement Of the Basic Materials Of The Study (Methods And Obmentioning
confidence: 99%
“…Lately, the effectiveness of synthetic antioxidant N-acetylcysteine (NAC) for correction of cardiovascular diseases in experiments in vivo has been actively discussed [7,8]. The recent systemic review has also pointed out that NAC has cardioprotective potential in case of hyperglycemia-induced OS [9].…”
Section: Analysis Of Recent Studies and Publications In Which A Solutmentioning
confidence: 99%